ENKULTURASI BUDAYA PESANTREN DALAM KITAB AL-IKLĪL FI MA’ĀNĪ AT-TANZĪL KARYA MISHBAH MUSTHOFA - Rohman, Nur (SUHUF, 2019)
This study observes the dialogue of pesantren (Islamic boarding schools) being held by Mishbah Musthofa (1916-1994) to understand the deeper meaning of the Qurâ€™anic verses of being reflected in exploring the meaning of the verses of the Qur'an as reflected in his Qurâ€™anic interpretation of al-IklÄ«l fÄ« MaÊ»ÄnÄ« at-TanzÄ«l, particularly when it is seen from the aspect of the pesantren tradition. The approach used is known as cultural enculturation, a perspective which emphasizes the dialectic of revelation (the Qurâ€™an) and local culture. The results of the study showed that there were two response models in their interpretations. The first is to adopt in order to complement (adoptive-complement). It can be seen by the attitude of accepting the tradition which is developed in the pesantren. For example the use of Pegon scripts (Arabic script in Javanese language), yellow books and religious traditions. The second is to adopt in order to reconstruct (adoptive-reconstructive). It is shown through his critical attitude towards some pesantren traditions. For example, Misbah Musthofaâ€™s critique to the tradition of respecting (ta?z?m) the kiai, tarekat tradition, refusing the Qur'anic reciting competition (Musabaqah Tilawatil Qurâ€™an), and praying by using loudspeakers. This study confirms the integration between pesantren culture and interpretation in the process of interpreting the Qur'an.